Upaya Peningkatan Pengelolaan Melalui Pendekatan Manajemen Operasional pada UMKM Sayur Balap di Carenang - Nova Yuliana; Juliani Zean; Sofihah Sofihah; Aris Rizki (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This research examines efforts to improve operational management at Sayur Balap MSMEs in Carenang through an operational management approach. Using qualitative methods, data was collected through semi-structured interviews via WhatsApp and direct observation to identify obstacles in transportation, operational management and stock management. The results of the thematic analysis show the challenges faced and improvement strategies that can be implemented. This research aims to provide practical recommendations to improve operational efficiency and competitiveness of MSMEs in the agricultural sector.